Common Size Analysis as a Tool for Measuring the Financial Performance of PT. Bank Sumut Head Office in the 2023–2024 Period - Budiarta Budiarta; Sugiyanto Tanoto (Journal of Managerial Sciences and Studies, 2025)
This study aims to analyze the financial performance of PT. Bank Jatim using the common size method based on its financial statements for the period 2023-2024. The research adopts a descriptive quantitative approach with secondary data derived from audited financial reports. The common size method was applied to both the balance sheet and income statement to evaluate changes in the proportion of assets, liabilities, equity, revenues, and expenses relative to their totals. The results indicate that PT. Bank Jatim experienced consistent growth in total assets, primarily driven by the expansion of third-party receivables. On the liabilities side, third-party funds (DPK) also showed a steady increase, reflecting strong public trust and the effectiveness of the bank’s funding strategies. Meanwhile, the income statement analysis revealed that operating revenues, dominated by loan interest income, demonstrated growth; however, operational expenses—particularly administrative and personnel costs—also increased, exerting slight pressure on net income margins. Overall, the findings suggest that PT. Bank Jatim maintained sound financial performance throughout the study period, with healthy asset growth and revenue generation. Nonetheless, the rising trend in operational expenses highlights the importance of improving cost efficiency. This study recommends that PT. Bank Jatim adopt stricter cost control measures, diversify revenue sources beyond loan interest income, strengthen its capital base, and accelerate digital transformation to enhance competitiveness.